2022
DOI: 10.11591/ijece.v12i2.pp2001-2013
|View full text |Cite
|
Sign up to set email alerts
|

Automatic missing value imputation for cleaning phase of diabetic’s readmission prediction model

Abstract: Recently, the industry of healthcare started generating a large volume of datasets. If hospitals can employ the data, they could easily predict the outcomes and provide better treatments at early stages with low cost. Here, data analytics (DA) was used to make correct decisions through proper analysis and prediction. However, inappropriate data may lead to flawed analysis and thus yield unacceptable conclusions. Hence, transforming the improper data from the entire data set into useful data is essential. Machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The intuitive way to deal with missing data is the deletion of the features or instances containing missing values [5]- [7]. However, this method has risks of losing important information in datasets, and it can significantly impact classification accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intuitive way to deal with missing data is the deletion of the features or instances containing missing values [5]- [7]. However, this method has risks of losing important information in datasets, and it can significantly impact classification accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Int J Artif Intell ISSN: 2252-8938  Hoque et al [5] have compared the imputation accuracy of many machine-learning-based methods. They found that adaboost classifier and linear support vector machine (SVM) are better than logistic regression (LR), and random forest (RF).…”
Section: Introductionmentioning
confidence: 99%